2020
DOI: 10.1175/jcli-d-19-0229.1
|View full text |Cite
|
Sign up to set email alerts
|

Near-Global Atmospheric Responses to Observed Springtime Tibetan Plateau Snow Anomalies

Abstract: Previous studies show that there are substantial influences of winter–spring Tibetan Plateau (TP) snow anomalies on the Asian summer monsoon and that autumn–winter TP heavy snow can lead to persisting hemispheric Pacific–North America-like responses. This study further investigates global atmospheric responses to realistic extensive spring TP snow anomalies using observations and ensemble transient model integrations. Model ensemble simulations are forced by satellite-derived observed March–May TP snow cover e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…It is worthy to note that the spatial distribution of atmospheric circulation anomalies over the North Pacific in Figures 5A,B shows a North Pacific Oscillation/western Pacific (WP)-like structure. Previous studies have already reported that the TP snow cover anomalies can lead to a WP-like response (e.g., Wang Z. et al, 2017;Liu et al, 2020). Why did the ONDJ TP snow forcing trigger a winter PNA response in 1979-1998 but a WP response in 1999-2016?…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is worthy to note that the spatial distribution of atmospheric circulation anomalies over the North Pacific in Figures 5A,B shows a North Pacific Oscillation/western Pacific (WP)-like structure. Previous studies have already reported that the TP snow cover anomalies can lead to a WP-like response (e.g., Wang Z. et al, 2017;Liu et al, 2020). Why did the ONDJ TP snow forcing trigger a winter PNA response in 1979-1998 but a WP response in 1999-2016?…”
Section: Discussionmentioning
confidence: 95%
“…Wang et al (2020) detected that the impact of the TP snow cover on the North America SAT in spring experienced a weakening in the mid-2000s. In addition, observational and numerical studies suggest that the TP snow anomaly can trigger near-global atmospheric circulation patterns, such as the Pacific-North American (PNA)-like teleconnection (e.g., Lin and Wu 2011;Wu et al, 2011;Liu et al, 2017) and the Western Pacific-like teleconnection (e.g., Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the thermal forcing of the TP, which may be related to local SAT anomalies, in turn, exert important influences on SSTAs in some areas of the Pacific and Indian Oceans [51][52][53]. The TP thermal anomaly may result in an asymmetrical response of the East Asian summer monsoon to the quadrennial oscillation of global SSTAs through the TP thermal feedback [54]. That is, the prediction of the summer eastern TP SAT involves complex air-sea interaction processes.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Empirical orthogonal function (EOF) analysis is used to capture the spatiotemporal variations of the CGT instead of the one-point correlation. The first two dominant related modes between diabatic heating over the TP and the surrounding area and H200 are detected by the SVD method (Bretherton et al 1992;Liu et al 2020a;Wallace et al 1992). Linear regression and composite analysis are conducted to obtain the circulation patterns related to the diabatic heating over the TP, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Robust connections have been found between the atmospheric circulation and the variability in snow cover on the TP (Song et al 2019;Zhao et al 2007;Wu et al 2014a, b). Autumn-spring snow cover over the eastern TP can affect North American temperature by largescale atmospheric wave pattern, a Pacific-North America (PNA)-like downstream atmospheric response, and a western Pacific-like teleconnection pattern is excited by anomalies in the autumn snow cover (Lin and Wu 2011;Liu et al 2017Liu et al , 2020aMote and Kutney 2012;Qian et al 2019;Wang et al 2020;Wu et al 2011). The decrease in summertime snow cover can trigger a zonal wave train over Eurasia and influence 30% of the total variance in summer heat waves in southern Europe (Wu et al 2016c).…”
Section: Introductionmentioning
confidence: 99%